Preparation of Polyvinylidene Fluoride Membrane with Functional Anthraquinones for Nitrogen Removal. (May 2018) - Qian, Ye; Yuping, Wang; Meilan, Xu; Wenchao, Liao; Bin, Yan
Abstract: This study relates to a method for preparation of polyvinylidene fluoride membrane with functional anthraquinones. The method is carried out according to the following steps: step 1: preparing 2- (1- hydroxy -3- butene) -1, 4, 5, 8- tetramethoxyl naphthalene; step2: preparing polyvinylidene fluoride-aromatic ether copolymers: polyvinylidene fluoride was used as the initiator, 2-(1-hydroxy-3-butene) -1, 4, 5, 8-tetramethoxynaphthalene was the monomer, N, N-dimethylformamide was solvent, cuprous chloride / Me6TREN was the catalytic, polyvinylidene fluoride-aromatic ether copolymer was synthesized by atomic transfer radical polymerization; step3: reducing the polyvinylidene fluoride-aromatic ether copolymer to quinone by demethoxy oxidation; step4: using the product of step3 and N, N- dimethylformamide as film-forming reagents, then scraping into a membrane. These functional membranes can effectively solve the problem of fixation of redox mediator and improve the efficiency of treatment of wastewater with high nitrogen concentration.